Diabetes in Pregnancy: Maternal Profile and Neonatal Outcome (Delta Medical College Journal, 2016)
Background: Diabetes in pregnancy is associated with increased risk to the woman and to the developing fetus. Historically, infants born to mother with diabetes (IDM) have significantly greater risk for spontaneous abortion, stillbirth, congenital malformations and perinatal mortality and morbidity.Objective: To evaluate the complications associated with diabetes in pregnancy in the periconceptional, fetal, neonatal and postnatal period.Materials and method: This observational study was carried out in the department of Obstetrics & Gynaecology of Bangladesh Institute of Research & Rehabilitation in Diabetes, Endocrine & Metabolic Disorders (BIRDEM), Dhaka, Bangladesh, from July 2013 to December 2013. Data of 100 patients with pregestational diabetes mellitus (PGDM) and gestational diabetes mellitus (GDM) delivering live baby after 37 completed weeks were evaluated during the period. They were divided into two groups: patients with PGDM in group-A and patients with GDM in group-B.Results: Majority of the PGDM patients were in 31-35 years age group whereas 50% of the GDM patients were from younger group (26-30). A major proportion of the patients of both the groups required Caesarean section with a higher rate in group-A. Diabetic mothers had more macrosomic babies than GDM mothers (14% vs 4%). Most commonly found neonatal complications were hyperbilirubinaemia followed by RDS and hypoglycaemia in both the groups with a higher proportion in PGDM group.Conclusion: Almost similar maternal and neonatal complications were observed in both PGDM and GDM group in our study despite of integrated antenatal, intranatal and perinatal care with a higher proportion in PGDM patients.Delta Med Col J. Jul 2016 4(2): 83-88